Détermination des paramètres de la machine synchrone à pôles saillants par les essais indiciels - DAHMANI Saad; BLAIDI Yassine; DAREM El Moradj (UNIVERSITE Amar Telidji de Laghouat.FACULTE DE TECHNOLOGIE.DEPARTEMENT D’ELECTROTECHNIQUE, 2021)
Abstract: In these theses we have approached the synchronous machine in order to be able to study the phenomena linked to its operating regimes. As a result, we have proposed assemblies which allow index tests to be carried out in order to be able to determine the parameters, transient and permanent regime of a synchronous machine with smooth poles.
OPTION : MACHINES ELECTRIQUES